A critical analysis of the use of blended finance for public infrastructure development in South Africa: The IIPSA Case Study - Kopeledi, Mosa (Graduate School of Business (GSB), 2023)
Public-Private Partnerships (PPPs) are a commonly used procurement strategy, adopted to advance the achievement of national developmental goals. The transactions match the efficiency of the private sector, with the large market potential of the public sector, to establish mutually beneficial partnerships and address increasingly growing public infrastructure development demand. Blended finance, as a subject on alternative financing for public infrastructure finance, has gained popularity in developing counties with poor balance sheets and deteriorating sovereign credit ratings, as an option to raise capital to address infrastructure backlogs and developmental challenges by creating commercially viable public infrastructure markets for sustainable development. However, the results on blended finance transactions and initiatives have not realised the benefits purported for the adoption of blended finance in developing countries. This study sought to critically explore the perceptions of stakeholders on the outcomes of blended finance in the Infrastructure Initiative Programme for Southern Africa (IIPSA) programme. A qualitative research method approach is utilised to explore the factors that advanced or hindered the achievement of the objectives of IIPSA, and based on their experience, further identifies CSF for the adoption of blended finance in South Africa. The thematic analysis utilized in the study, reveals that participants do not believe that the objectives of IIPSA were met due to a Mis- alignment in expectations between the European Union and the SA stakeholders. Governance, State Capacity, DFI mandate restriction, Ambiguous communication of programme objectives, Misalignment in Expectations, Resistance to change, Performance measure, Regulatory restrictions, and an Unstable political environment constitute the nine main themes to emerge from the analysis of factors that hindered the achievement of IIPSA objectives. The CSF are organized around six main themes of Context, Institutional Capacity & Coordination, Alternatives to blended finance, Transparency, Motives, and Environment. The study recommendations are categorized at the Country level, where environmental factors are fundamentally at play, the Institutional Capacity level, where the competency factors of the implementing institutions are highlighted, and at the Project level, where the study relates these to motivation factors of the stakeholders.